(untitled) (EAAE Annual Conference Proceedings, 2019)
Who makes the architecture first, Ariadne with her thread defining a place, or Daedalus making the labyrinthine space? What makes the educational process, not the bright new shiny buildings (space), but the bodies of students, travelling on their overlapping educational journeys (place)? So Samsonite suitcases at the ready. This paper will explore the hidden, implicit relationship between space and place in architectural education, not in the physical (architectural school) but as the locating of process in architectural research.